Reducing Flight Delays and Disruptions in Airline Operations - Kopchenova, Kseniia; Martínez, Felipe; Rathouský, Bedřich; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This Bachelor's thesis examines the causes of flight delays and disruptions in airline operations and proposes practical solutions to enhance operational efficiency. Using Failure Mode and Effects Analysis (FMEA), the study systematically identifies key areas of concern and provides improvement proposals to mitigate these challenges. By analyzing various causes of flight delays, this research offers valuable insights into the factors affecting airline operations. The proposed improvement actions aim to reduce flight delays, improve on-time performance, and enhance customer satisfaction within the aviation industry.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses